The effect of HPMC-K15M and guar gum as polymer-coated for sustained-released tablet: disintegration and release kinetics - Nining, Nining; Amalia, Anisa; Riyanto, Raditya Naufal (Pharmaciana, 2024)
Polymeric coating films are able to control tablet drug release rate depending on polymer physicochemical properties. Guar gum and HPMC-K15M (GG/HPMC-K15M) can be a coating polymer in sustained-release tablets. This study aims to characterize the disintegration and drug release kinetics on theophylline sustained-release tablets coated with GG/HPMC-K15M. The film coating was made with variations of the GG/HPMC-K15M ratio of 1:3 (F1), 1:4 (F2), and 1:5 (F3). Granules were preformulated regarding LOD, granule size distribution, packing, and flow properties. Film coating was carried out using a liquid spraying method. Coated tablets were tested for quality examination, and the drug release kinetics model was determined based on in-vitro dissolution. Granule pre-formulation result shows that the granules have excellent packing and flow properties with an LOD of 4.59–5.33% and a size of 553.28–627.28 πm. Tablets provided uniform size characteristics with a weight variation of 333.38–339.56 mg (CV 1.32–3.43% and acceptance value 6.53–13.58), hardness of 11.61–18.86 kgf, friability of 0.103–0.186%, disintegration time of 20.69–27.36 min, and drug content of 98.51–98.55%. The theophylline was dissolved by 95.24% (6h in FI), 97.04% (7h in F2), and 99.79% (8h in F3); all formulas followed zero-order kinetic (r2 ~ 1). Suitable quality theophylline tablets GG/HPMC-K15M coating have been successfully produced. Increasing the concentration ratio of HPMC-K15M in the coating solution resulted in a significant increase in disintegration time and a slowing of the drug release rate. The drug release kinetics of all formulations followed the zero-order kinetic model.